Economic incongruities in the European patent system - Malwina Mejer; Bruno Van Pottelsberghe de la Potterie (Bruegel, 2009)
This paper argues that the consequences of the 'fragmentation' of the European patent system are more dramatic than the mere prohibitive costs of maintaining a patent in force in many jurisdictions. First, detailed analysis of judicial systems in several European countries and four case studies provide evidence suggesting that heterogeneous national litigation costs, practices and outcome induce a high level of uncertainty. Second, a high degree of managerial complexity results from systemic incongruities due to easier 'parallel imports', possible 'time paradoxes' and the de facto paradox of having EU-level competition policy and granting authority ultimately facing national jurisdictional primacy on patent issues. These high degrees of uncertainty and complexity contribute to reduce the effectiveness of the European patent system and provide additional arguments in favour of the Community patent and a centralized litigation in Europe.
Keywords: K41; P14; O34; 330; European patent system; patent cost; litigation process; enforcement; uncertainty; Patentrecht; Nationales Recht; Zivilprozess; Prozesskostenrechnung; Risiko; Markteffizienz; EU-Recht; EU-Staaten